Aktivasi Neurohormonal dan Remodeling Atrium Kiri pada Stenosis Mitral - Vidya Gilang Rejeki; Bambang Budi Siswanto; Nani Hersunarti (The Indonesian Heart Association, 2016)
Mitral stenosis is closely related with the hemodynamic consequences of obstructed mitral leaflet. Definitive therapy in mitral stenosis is mechanical intervention. Late presentation of mitral stenosis patients to medical facilities due to limited health facilities and Indonesian’s demographic, often make patients’ condition deteriorates, in which intervention need to be delayed or even no longer suitable. Stretched left atrium and reduced cardiac output stimulate several neurohormonal activation; renin-angiotensin-aldosterone and symphatetic nervous system. Left atrial remodeling further worsen hemodynamic ststus. Renin-angiotensin-aldosterone and sympathetic blockage could improve mitral stenosis patients’ condition with close observation to hypotension status.